Social Risk and Protective Factors in Adolescents' Reduction and Cessation of Alcohol Use. (7th June 2017) - Cheng, Tyrone C.; Lo, Celia C.
ABSTRACT: Background: Adolescents' alcohol use is related to many health problems, injuries, and violent acts, some with fatal consequences. A gap exists in the literature discussing risk/protective factors in change from non-heavy drinking to non-drinking, and also for change from heavy drinking to non-heavy drinking or non-drinking. Objective: This secondary study examined some risk and protective factors involved when adolescent non-heavy drinkers and adolescent heavy drinkers curb or terminate their drinking. Method: The temporal-ordered analysis evaluated 570 nonheavy drinkers and 374 heavy drinkers (all adolescents), a sample extracted from Wave 1 and Wave 2 of the National Longitudinal Study of Adolescent to Adult Health, or Add Health. Results: We observed positive associations between likelihood of change from heavy/non-heavy drinking to nondrinking and 5 characteristics: neighborhood attachment, maternal receipt of public assistance, African American ethnicity, maternal involvement, physical maltreatment, depressive feelings, and substance-abuse treatment. We observed negative associations between this outcome and peer drinking, delinquent behaviors, drug use, and emotional maltreatment. Positive associations were found between likelihood of change from heavy drinking to non-heavy drinking and both maternal involvement and depressive feelings, while a negative association was found between this outcome and delinquent behaviors. Conclusions: Reduction/cessation interventions should, at the individual level, focus on ending adolescent drinkers' associations with alcohol-using and delinquent peers. Interventions require supportive roles for parents, schools, and communities.